(untitled) (Praxis Educativa, 2023)
The objective of this article is to describe the process of transferring the Psychological Wellbeing Information and Monitoring System (hereinafter SIS-BP) in secondary schools in Tarapacá, northern Chile. First, theoretical and contextual background on psychological well-being in education and on transfer in the Chilean school context are exposed. Second, following the Bozeman transfer model, the SIS-BP transfer process carried out with the schools is described. At the end, we reflect on the implications of the transfer from the social sciences to the educational context based on SIS-BP experience.